Pengaruh Faktor Kualitas dan Harga Produk terhadap Keputusan Pembelian pada Marketplace Tokopedia - Anggun Resya Widianingrum; Rafikhein Novia. A (Jurnal Manajemen Bisnis Digital Terkini, 2025)
Consumer behavior, especially in online shopping, has evolved significantly due to advances in digital technology. The researcher aims to examine how price and product quality affect customer purchases on Tokopedia. A quantitative research approach was used, involving 52 active Tokopedia users as respondents. Data were analyzed using multiple linear regression through IBM SPSS version 29. The findings show that product quality and price have a significant influence and lead to a positive impact in shaping consumer purchasing decisions. Between the two, price has a greater influence, with a coefficient value of 0.413 compared to 0.272 for product quality. The R² value of 0.419 indicates that both elements contribute 41.9% of the variance in purchasing decisions. These results highlight the importance of a competitive pricing strategy and providing products that meet customer expectations to drive sales on digital platforms. However, other elements such as customer reviews, service quality, and seller reputation should also be considered to support better purchasing decisions.